Shake table tests of seven-story reinforced concrete structures with torsional irregularities: Test program and datasets. Issue 4 (November 2021) - Suzuki, Tomomi; Puranam, Aishwarya Y; Elwood, Kenneth J; Lee, Hung-Jen; Hsiao, Fu-Pei; Hwang, Shyh-Jiann
The shake table tests presented in this article aims to explore seismic displacement demands for existing reinforced concrete buildings resulting from inelastic torsion associated with different sources of irregularities. Two half-scale seven-story reinforced concrete structures were subjected to unidirectional earthquake excitations on the shake table at the National Center for Research on Earthquake Engineering (NCREE) Tainan laboratory. The specimens reflected structural weaknesses of buildings which collapsed during the Meinong earthquake in Taiwan. This data paper presents an overview of the project as well as the organization of obtained test datasets. The data are available for public use under the Designsafe-CI project "Shake table tests of seven-story reinforced concrete structures with torsional irregularities."